(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Creating the image of the company in this day and age is no longer a fad business, but part of an integrated marketing communication. The positive image of the company is based not only on positive feelings and emotions of the customer associated with them, but also agreat tool of image policy. In crisis situations addressed adequately image strategy is the optimal solution, and very often the only solution to their survival. Market Practice shows that each company is taking active steps dialect appropriate image creation, and then effectively manages it.